Anatomical Structure of Sepal and Petal of Red Dragon Fruit (Hylocereus polyrhizus Britton & Rose) During Flower Development - Utaminingsih Utaminingsih; Sulhan Etfanti; Suharyanto Suharyanto; Maryani Maryani (UIN Sunan Gunung Djati Bandung, 2019)
Red dragon fruit (Hylocereus polyrhizus Britton & Rose) is one type of cactus plant which is very potential as an ornamental plant and edible fruit. Flower is organ that play an important role in the process of breeding plants generatively. This reasearch aimed to study the anatomical structure of sepals and petals of red dragon fruit plants during flower development. The research stages included: sepals and petals sampling that held at various stages of flowering ; morphological observation (measurement length of sepals and petals); anatomical slides of sepals and petals cross section using the embedding method, anatomical observation and image capture of sepals and petals. The parameters observed were bud size, sepal length, petal length, sepal thickness, petal thickness, and tissue description composed. The results of this study indicated that buds have an increased development pattern. The increase in bud size is directly proportional to the stage of the bud. Sepal and petal are composed of epidermal tissue which form papillae, cryptophore stomata, secretory parenchyma space containing mucus, and tissues transport system is closed collateral.